2016
DOI: 10.1016/j.bbrep.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Secreted factors from adipose tissue-derived mesenchymal stem cells suppress oxygen/glucose deprivation-induced cardiomyocyte cell death via furin/PCSK-like enzyme activity

Abstract: Clinical application of mesenchymal stem cells (MSCs) represents a potential novel therapy for currently intractable deteriorating diseases or traumatic injuries, including myocardial infarction. However, the molecular mechanisms of the therapeutic effects have not been precisely revealed. Herein, we report that conditioned media (CM) from rat adipose tissue-derived MSCs (ASCs) protected adult cardiomyocytes from oxygen/glucose deprivation (OGD)-induced cell death. We focused on furin/PCSK protease activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…For example, Sadat et al (34) reported that in an in vitro neonatal rat cardiomyocyte and ASC co-culture system, the anti-apoptotic effect of ASCs was observed under hypoxic conditions (a humidified atmosphere with 95% N 2 and 5% cO 2 gas mixture). Consistent with the results of the present study, a previous study demonstrated that the ASCs markedly suppressed oxygen deprivation-induced cardiomyocyte cell death, and the oxygen content in their cell culture condition was also set as 5% O 2 (35). To the best of our knowledge, the present study is the first report directly comparing the beneficial effects of ASCs under normoxia and physioxia on ventricular myocytes following oxidative stress.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Sadat et al (34) reported that in an in vitro neonatal rat cardiomyocyte and ASC co-culture system, the anti-apoptotic effect of ASCs was observed under hypoxic conditions (a humidified atmosphere with 95% N 2 and 5% cO 2 gas mixture). Consistent with the results of the present study, a previous study demonstrated that the ASCs markedly suppressed oxygen deprivation-induced cardiomyocyte cell death, and the oxygen content in their cell culture condition was also set as 5% O 2 (35). To the best of our knowledge, the present study is the first report directly comparing the beneficial effects of ASCs under normoxia and physioxia on ventricular myocytes following oxidative stress.…”
Section: Discussionsupporting
confidence: 89%
“…It has been reported that MSC co-culture/co-transplantation may enhance the therapeutic effect of cells of interest, such as cells of the liver 9 and myocardium. 48 Similarly, in pancreatic islets, the inhibition of apoptosis and enhancement of insulin secretory capacity of cultured Representative images (A). Colony-forming efficiency of cells (%) in CFU assay (B).…”
Section: Discussionmentioning
confidence: 99%